Accessing ultrastable glass via a bulk transformation - Hengtong Bu; Hengwei Luan; Jingyi Kang; Jili Jia; Wenhui Guo; Yunshuai Su; Huaping Ding; Hsiang-Shun Chang; Ranbin Wang; You Wu; Lingxiang Shi; Pan Gong; et al. (Nature Communications)
Abstract As a medium to understand the nature of glass transition, ultrastable glasses have garnered increasing attention for their significance in fundamental science and technological applications. Most studies have produced ultrastable glasses through a surface-controlled process using physical vapor deposition. Here, we demonstrate an approach to accessing ultrastable glasses via the glass-to-glass transition, a bulk transformation that is inherently free from size constraints and anisotropy. The resulting ultrastable glass exhibits a significantly enhanced density (improved by 2.3%), along with high thermodynamic, kinetic, and mechanical stability. Furthermore, we propose that this method of accessing ultrastable glasses is general for metallic glasses, based on the examination of the competitive relationship between the glass-to-glass transition and crystallization. This strategy is expected to facilitate the proliferation of the ultrastable glass family, helping to resolve the instability issues of glass materials and devices and deepen our understanding of glasses and the glass transition.